René L. Schilling, Mass und Integral - Eine Einführung für Bachelor-Studenten, x+172 pp, Walter de Gruyter, Berlin/Bsoton, 2015, ISBN: 978-3-11-034814-9/pbk; eISBN(PDF): 978-3-11-035064-7; eISBN(EPUB): 978-3-11-038332- - LISEI, Hannelore Lisei (Studia Universitatis Babeș-Bolyai Mathematica, 2016)
This is a text of a course on measure theory and integration for students in mathematics and physics. The main goal of the book is to present the basic properties of the Lebesgue measure and integral needed in higher analysis, probability theory and mathematical physics.